Character Ambiguity: Searching For New Approach To Islamic Education Textbooks - Akhmad Affandi; Nurun Nufus; Zahira Jannataini; Nida Wafa (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This research is based on the reality that character education in Islamic education textbooks remains inadequate, even though character education is crucial in shaping students with noble character and the ability to face moral challenges in the modern era. Character, as part of affective competence, must be taught clearly and consistently, just as cognitive and psychomotor competencies, to achieve balance in forming a complete and ideal personality. This study was conducted on Islamic Education textbooks for 11th grade used in schools across Indonesia, published by the Ministry of Education, Erlangga, Grafindo, and Tiga Serangkai. Using a qualitative approach, these textbooks were analyzed through content analysis to identify the extent to which character education values are integrated into them. The results show that all textbooks used as subjects in this study have not fully integrated character education optimally. Character education must be implemented by considering appropriate objectives, materials, methods, media, and evaluation.Keywords: Character Education, Affective Domain, Learning Components.